(3QSGFds ((3UObg Hf Sdeg Hf eMeO Hf Ydi Hf jYbhH Hf eMeO GdeUQi s)
(3ChdgG (B:s
(3eHJhQ hChd GdehLhO efgG(B: (3hSjha bhGWH , hQeGM fSjH OhGfjgG ef GdOfjG ZhGVH s
(3BNQgG (B:s
(3ajG HMQ gd dj hQhO Ydjc dYdi CZSd gPG GddSGf hef PG jWjb s
(3HBNQ UaMGJgG JYbjHIs
(3dCMO GdefTFjf ai GdOhGhjf ef QLGd GdbQf GdKGef GdgLQis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs